Cash flow optimization for construction engineering portfolios - Ali, Gasser Galal (AUC Knowledge Fountain, 2016)
One of the main issues in construction projects is finance; proper cash-flow management is necessary to insure that a construction project finishes within time, on budget, and yielding a satisfying profit. Poor financial management might put the contractor, or the owner, in a situation where they are unable to finance the project due to insufficient liquidity, or where they are engaged in excessive loans to finance the project, decreasing the profit, and even creating unsettled debts. Engagement with a portfolio of large construction projects, like infrastructure projects, makes attention to finance more critical, due to large budgets and long project durations, which also requires attention to the time value of money when the project spans over many years and the work environment has a high inflation rate. This thesis aims at the analysis and optimization of the cash-flow request for large engineering portfolios from the contractor's point of view. A computational model, with a friendly user interface, was created to achieve that. The user is able to create a portfolio of projects, and create activities in them with different relationship types, lags, constraints, and costs, as similar to commercial scheduling software. Parameters necessary for the renumeration are also considered, which include the down payment percentage, duration between invoices, duration for payment, retention percentage, etc. The model takes into consideration the time value of money, calculated with an interest rate assigned to the projects by the user; this could be the inflation rate or the (Minimum Attractive Rate of Return) MARR of the contractor. Optimization is done with the objective of maximizing the Net Present Value (NPV) for the projects as a whole, discounted at the start of the portfolio. The variables for the optimization are lags that are assigned for each activity, which, after rescheduling, delays the activities after their early start with the value of those lags, and thus creates a modified cash flow for the project. Optimization of those variables, within scheduling constraints results in a near-optimum NPV. Verification of the model was done using sets of portfolios, and the validation was done using an actual construction portfolio from real life. The results were satisfactory and matched initial expectations. The NPV was successfully optimized to a near optimum. A sensitivity analysis of the model was conducted and it showed that the model behaves as expected for different inputs. A time test was performed, taking into consideration the effect of the size and complexity of a portfolio on the calculation time for the model, and it showed that the speed was satisfactory, though it should be improved. Overall, the conclusion is that the model delivers its goal of maximizing the Net Present Value of a large portfolio as a whole.